Pioneirismo revelado: o trabalho educativo das filhas da caridade em são José de Ribamar- Ma (1944-1952) - AMORIM, Rosiane Silveria Rodrigues Veloso (2017)
This dissertation, written in the perspective of Cultural History, brings an approach to the work of religious women, specifically the Daughters of Charity of Saint Vincent de Paul in education maranhão. The historical and geographic context is the municipality of São José de Ribamar - MA, where the development of the charitable work of these women contributed significantly in the provision of instruction for girls and boys, in a given time cut in which the public power did not assume its responsibility as an effective body of public policies for this social segment. Hence the research proposes to analyze the performance of these sisters in the educational field, as well as, to increase the knowledge about the history of ribamarian education, whose relationship is intrinsically linked to the performance of the Vincentians. On the methodology, we characterized our research as bibliographical and qualitative, having as sources: documents of the Sanctuary of St. Joseph of Ribamar (ecclesiastical book - book Tombo) and the Company of the Daughters of Charity in São José de Ribamar and São Luís. we also use iconographic documents. In the theoretical contribution we highlight the following authors: Flinton (1989); Azzi (2008); Coelho (2001); Dodin (1980); Manoel (1999;2001) and Priore (2011; 2013). The temporal milestones we refer to are from 1944 to 1952, the period of establishment of the Company in the locality and the presence of the first Superior Sister in front of the work in the community. Thus, it is a research that seeks to insert in the field of women's history, these religious as historical subjects, giving them not only the deserved visibility, but highlighting their role as protagonist as evidencing their main characteristic of pioneers. Pioneirismo this that passes all the work of the Company since its origin, passing through the Ultramontane Movement that provided its migration to Brazil, until arriving in the territory of Maranhão. Therefore, when we bring this micro look of history, we enable the expansion of knowledge about education from the religious point of view, in the gender bias. In order to do so, we dialogue with authors who discuss Gender, Education and Religion, in order to understand how these fields are articulated and allows us to sharpen a more critical view of social groups.